Advances in structured operator theory and related areas : the leonid lerer anniversary volume - Rodman, Leiba; Woerdeman, Hugo J.; Kaashoek, Marinus A. (Operator Theory: Advances and Applications, 2013)
This volume is dedicated to Leonid Lerer on the occasion of his seventieth birthday. The main part presents recent results in Lerer's research area of interest, which includes Toeplitz, Toeplitz plus Hankel, and Wiener-Hopf operators, Bezout equations, inertia type results, matrix polynomials, and related areas in operator and matrix theory. Biographical material  and Lerer's list of publications complete the volume.